“It is better to build a bridge…” Using the praxis cycle of Holland and Henriot in discerning an African Reformed missional ecclesiology - Nel, RW (Nederduitse Gereformeerde Teologiese Tydskrif, 2014)
Reformed churches in Africa need bridge-building, uniting ecclesiologies. From the challenges on local congregational, but also at denominational level, it seems as if ecclesial apartheid (sadly) remains. From an (Southern) African Reformed perspective, I argue however that all is not lost. The question is how can our different theologies bridge these gaps? In this respect, the current conversations on “missional” and “emergent church” may be signs of hope. These notions can play a key role in bridging this gap between an ecclesiocentric, colonial ecclesiology and postcolonial ecclesiologies, which discern the Missio Dei afresh in the contemporary context. In my recent doctoral research I took up this challenge and used an adapted or what I prefer to call a “remixed” version of a praxis methodology to develop postcolonial (Southern] African missional ecclesiologies. I reflect on the usage of this methodology in order to make proposals on its relevance in the wider discourse on developing African missional ecclesiologies.